Robustness of quantum coherence and quantum criticality in spin-1 many-body system - Wajid Joyia; Khalid Khan; Asif Ilyas; M.A. Khan (Physics Open, 2023)
The tripartite quantum coherence for spin-12 and bipartite quantum coherence for spin-1 many-body systems are studied with the quantum renormalization group method to investigate the quantum criticality behaviour of both systems. We find both spin-12 and spin-1 systems exhibit quantum criticality behaviour after different number of iterations. However, the bipartite quantum coherence for spin-1 system reaches the quantum criticality behaviour in lesser number of iterations than the tripartite quantum coherence for spin-12 system. The quantum criticality behaviour of both systems is also investigated through non-analytic and the scaling behaviour of quantum coherence. Additionally, quantum correlations and quantum phase transition are observed to be more vigorous with higher spin comparatively to the number of parties (i.e., bipartite, tripartite, multipartite) involved in a quantum correlations.